O Frankenstein na sala de jantar : a interatividade e a narratividade no cruzamento entre a mídia de massa e a televisão digital - Breier, Lucilene (2006)
This work intends to understand the limits and the levels of interactivity in the digital television (DTV). For this reason, at first, it defines DTV as a hybrid medium, exploring the relations between the internet and traditional television in a complex perspective – as in Morin’s thinking. In a second part, we start our analysis focusing our attention in this relation at the narrative space. It’s where we check the interactive possibilities. In a complementary way, this work presents a historical research of interactive television implementation through the years.